2000
DOI: 10.1073/pnas.97.1.337
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors α and β in the rodent mammary gland

Abstract: An obligatory role for estrogen in growth, development, and functions of the mammary gland is well established, but the roles of the two estrogen receptors remain unclear. With the use of specific antibodies, it was found that both estrogen receptors, ER␣ and ER␤, are expressed in the rat mammary gland but the presence and cellular distribution of the two receptors are distinct. In prepubertal rats, ER␣ was detected in 40% of the epithelial cell nuclei. This decreased to 30% at puberty and continued to decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
156
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(172 citation statements)
references
References 33 publications
13
156
1
2
Order By: Relevance
“…A recent study describes coexpression of ERa and ERb protein in mouse mammary gland at di erent developmental stages (Saji et al, 2000). ERb protein has also been demonstrated to be expressed in rat cardiac myocytes and ®broblasts where ERa is also present (Grohe et al, 1997(Grohe et al, , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study describes coexpression of ERa and ERb protein in mouse mammary gland at di erent developmental stages (Saji et al, 2000). ERb protein has also been demonstrated to be expressed in rat cardiac myocytes and ®broblasts where ERa is also present (Grohe et al, 1997(Grohe et al, , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of estrogen receptor proteins in rat mammary gland has shown that both types of ERs are expressed and the results from ERα-KO and ERβ-KO mice reveal that ERα is necessary for mammary gland development. ERβ co-expression with ERα has been suggested to repress ERα's function and may contribute to the insensitivity of the mammary gland to estrogen during lactation [31,32]. Deletion of ERα, which mediates the E2 action in mice, results in a rudimentary ductal system that fails to branch out [33].…”
Section: E2 Signaling In Mammary Gland Developmentmentioning
confidence: 99%
“…Chicken polyclonal anti-ERb1 antibody, chicken polyclonal anti-ERb ins antibody, and rabbit polyclonal anti-ERbLBD antibody were produced in our laboratory. 11 Mouse monoclonal anti-NeuN antibody was from Chemicon (Temecula, CA, USA). Biotinylated anti-rabbit, anti-chicken, and anti-mouse antibodies raised in goats were from Zymed (South San Francisco, CA, USA).…”
Section: Chemicals and Antibodiesmentioning
confidence: 99%
“…After the discovery of ERb, 10 it became essential to reexamine the protein map of ERs in the CNS using antibodies that can selectively recognize ERa or ERb. 11 There have been several reports of ERa and ERb1 localization in the brain, 12,13 but a profile of receptor expression with age is lacking. In the previous IHC study from our group, using a highly specific antibody against ERb1 (ERb 503 IgY), we showed a highlevel expression of ERb1 14 and its importance during embryogenesis.…”
Section: Introductionmentioning
confidence: 99%